INFLUENCE OF LOCAL AND REGIONAL FACTORS CONTROLLING THE EVOLUTION OF THE MEGA PLATFORM IN THE CENTRAL LUCONIA PROVINCE, OFFSHORE SARAWAK - YUSLIANDI, ARI (2020)
During the Oligocene to Miocene, Southeast Asia was an equatorial region characterized by widespread attached and detached carbonate platforms. The Central Luconia Province represents a natural laboratory to study isolated carbonate platforms and understand the influence of numerous controls such as sea-level changes, tectonics, oceanographic circulation, climate changes, siliciclastic influx, and nutrition on platform evolution in the Southeast Asian region. In this study, parameters are classified based on the extent of their influence; local influence on single platforms or regional effect on the entire Central Luconia region. This is accomplished by a comprehensive analysis of seismic data integrated with sedimentological data from cored intervals.